2018
DOI: 10.1111/jam.13687
|View full text |Cite
|
Sign up to set email alerts
|

A mixture of Lactobacillus species isolated from traditional fermented foods promote recovery from antibiotic-induced intestinal disruption in mice

Abstract: Consumption of a mixture of Lactobacillus species may encourage faster recovery from antibiotic-induced gut dysbiosis and gut microbiota-related immune disturbance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 57 publications
3
39
1
Order By: Relevance
“…Although previous studies have shown that probiotics can promote intestinal barrier function and reduce intestinal inflammation, (24,62,(85)(86)(87)(88) in our studies only LR had this beneficial effect. Based on our current results, LR had the ability to alter the Firmicutes:Bacteriodetes ratio, strengthen intestinal barrier function, and reduce intestinal inflammation, whereas LGG did not.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…Although previous studies have shown that probiotics can promote intestinal barrier function and reduce intestinal inflammation, (24,62,(85)(86)(87)(88) in our studies only LR had this beneficial effect. Based on our current results, LR had the ability to alter the Firmicutes:Bacteriodetes ratio, strengthen intestinal barrier function, and reduce intestinal inflammation, whereas LGG did not.…”
Section: Discussioncontrasting
confidence: 77%
“…Previous studies have shown that increased intestinal permeability observed in diseases, such as IBD, is correlated with bone loss . Studies have also shown that ABX‐induced dysbiosis can affect intestinal permeability . Thus, we posited that ABX‐induced dysbiosis decreases bone health through altering intestinal permeability .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, mixtures of lactic bacteria obtained from fermented products restore the integrity of the microbiota by enhancing the gut barrier following an exposure to antibiotics in certain intervals [70]. There are novel techniques which facilitate the manipulation of the gut microflora by suppressing pathogens in the epithelium and intestines, in order to regulate the activity of immune cells [71].…”
Section: The Relevance Of Gut Microflora In Parkinson's Disease Pathomentioning
confidence: 99%